2010
DOI: 10.1002/jmv.21947
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of acute infection with parvovirus B19 genotype 2 in immunocompromised patients in Poland

Abstract: Parvovirus B19 (B19V) is divided into three genotypes. Genotypes 2 and 3 may cause diagnostic difficulties and their epidemiology is not well understood. In the present study the prevalence of B19V genotypes in patients with symptomatic infection in Poland was evaluated and the course of infection in patients infected with non-genotype 1 strains is described. Real-time PCR, able to detect all three genotypes of B19V was used to screen patient plasma samples. Sixty-nine, mainly acute-phase B19V DNA positive cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Reduction of immunosuppressive medication is often recommended in addition to IVIG (or without IVIG in less severe cases) to allow the patient's own immune response to mature and neutralize the virus (Bertoni et al, 1997;Lamont et al, 2011). Several reports have concluded that symptomatic B19V infection is linked specifically to the use of tacrolimus rather than the overall state of immunosuppression (Grabarczyk et al, 2011). This is based on the observations that a switch from tacrolimus to cyclosporine was followed by viral clearance and complete resolution of anemia in some patients (Pamidi et al, 2000).…”
Section: Treatmentmentioning
confidence: 99%
“…Reduction of immunosuppressive medication is often recommended in addition to IVIG (or without IVIG in less severe cases) to allow the patient's own immune response to mature and neutralize the virus (Bertoni et al, 1997;Lamont et al, 2011). Several reports have concluded that symptomatic B19V infection is linked specifically to the use of tacrolimus rather than the overall state of immunosuppression (Grabarczyk et al, 2011). This is based on the observations that a switch from tacrolimus to cyclosporine was followed by viral clearance and complete resolution of anemia in some patients (Pamidi et al, 2000).…”
Section: Treatmentmentioning
confidence: 99%
“…The prototype genotype 1a is the major circulating genotype and is present in all geographic areas [27]. The variant genotype 2 is rare but can be sporadically detected in different geographic settings including Europe [29][30][31]. The variant genotype 3, in its two subtypes, can be detected at higher frequency in western Africa, where it may constitute the prevalent genotype [23], and at lower frequencies in other geographic areas.…”
Section: Evolutionmentioning
confidence: 99%
“…15,16 Genotype 2 was presumably endemic in Northern Europe until half a century ago 16,17 and is sporadically found nowadays, e.g. in Poland, 18 South-Africa, 19 and Germany. 3 Genotype 3 was the only human Erythrovirus genotype detected in 13 DNA positive blood samples from 1000 volunteer blood donors in Ghana.…”
Section: Similar and Contrasting Cases In The Literature And Discussionmentioning
confidence: 99%